2012
DOI: 10.1073/pnas.1200194109
|View full text |Cite
|
Sign up to set email alerts
|

Secreted human glycyl-tRNA synthetase implicated in defense against ERK-activated tumorigenesis

Abstract: Although adaptive systems of immunity against tumor initiation and destruction are well investigated, less understood is the role, if any, of endogenous factors that have conventional functions. Here we show that glycyl-tRNA synthetase (GRS), an essential component of the translation apparatus, circulates in serum and can be secreted from macrophages in response to Fas ligand that is released from tumor cells. Through cadherin (CDH)6 (K-cadherin), GRS bound to different ERK-activated tumor cells, and released … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 53 publications
5
108
2
Order By: Relevance
“…Interestingly, extracellular wild-type GlyRS has previously been shown to decrease ERK phosphorylation in a time-and dose-dependent fashion in the human carcinoma cell line, HCT116, functioning as a tumor-defense system (19); however, consistent with our result (Fig. 7C), this effect was not observed in the human neuroblastoma cell line, SH-SY5Y (19).…”
Section: Mutant Glyrs Aberrantly Binds the Trk Receptors And Activatesupporting
(Expert classified)
See 1 more Smart Citation
“…Interestingly, extracellular wild-type GlyRS has previously been shown to decrease ERK phosphorylation in a time-and dose-dependent fashion in the human carcinoma cell line, HCT116, functioning as a tumor-defense system (19); however, consistent with our result (Fig. 7C), this effect was not observed in the human neuroblastoma cell line, SH-SY5Y (19).…”
Section: Mutant Glyrs Aberrantly Binds the Trk Receptors And Activatesupporting
(Expert classified)
“…neuropilin 1 (NRP1), which antagonizes VEGF signaling (18). This aberrant binding and noncell autonomous toxicity is contingent upon GlyRS secretion, which occurs from a number of different cell types in culture and is unaffected by neuropathyassociated mutations (17)(18)(19).…”
Section: Significancementioning
confidence: 99%
“…The proteomic data are consistent with previous studies that demonstrated that a similar dosage of Umb had an apoptotic effect on QU-DB cells, but not on A549 cells, and only after increasing the Umb dose was cytotoxicity observed in the A549 cells (2). Notably, certain upregulated proteins observed in each cell line in the current study (GRS in the QU-DB cells and calreticulin in the A549 cells) are known to interact with immune cells in vivo and boost anti-tumor immune response (32,36,37). This may indicate that Umb has stronger in vivo anti-tumor activities compared to in vitro results.…”
Section: Discussionsupporting
confidence: 86%
“…Immune stimulatory activity of GRS indicates its therapeutic potential against tumorigenesis. GRS is a component of the translation machinery, and is secreted from macrophages in response to Fas ligand, which is released from tumor cells (32). GRS binds to various extracellular signal-regulated kinase (ERK)-activated tumor cells and releases phosphatase 2A, which in turn suppresses ERK signaling through dephosphorylation of ERK and induces apoptosis (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation